The effect of the lock and key strategy on the achievement of first-year middle school students in social studies and their logical thinking (Journal of the College of Basic Education, 2025)
The current research aims to identify the effect of the lock and key strategy on the achievement of first-year middle school students in the subject of social studies and logical thinking. The sample of the current research was determined by second-year middle school students affiliated with the Second Rusafa Education Schools affiliated with Baghdad Governorate for the academic year (2024 - 2025). First-year middle school students were selected at: Palestine High School for the Distinguished for Boys to be its students as a research sample intentionally. Two halls were selected from a total of four halls of first-year middle school students, one of the two groups is experimental and the other is control. The research sample amounted to (70) students, with (35) students in the experimental group and (35) students in the control group. The researcher rewarded the two research groups in the variables of the intelligence test, chronological age, and logical thinking test. The achievement test was also prepared, as (35) paragraphs were formulated in accordance with the content of the material and behavioral purposes (cognitive, understanding, and application of the logical thinking test). A test was prepared by the researcher, which is logical thinking, which consisted of (15) paragraphs. The data were analyzed and processed statistically using the statistical program ( 21.SPSS.V), as the results showed that the students of the experimental group who studied with the lock and key strategy outperformed the students of the control group who studied with the usual method in the logical thinking test. Based on the results of the research, the researcher recommends the necessity of adopting the lock and key strategy in teaching the social studies subject because of its positive effect in increasing logical thinking among students. In order to verify the research objective, the researcher developed the following urban hypothesis:1-There are no statistically significant differences at a significance level of (0.05) between the average scores of the experimental group students who study according to the lock and key strategy, and the scores of the control group who study according to the usual method in achievement.2-There is no statistically significant difference at the level (0.005) between the average scores of the experimental group students who study using the (lock and key) strategy and the average scores of the control group students who study using the traditional method of logical thinking